L'analyse de contenu comme méthode d'analyse de la conception et de la qualité du logement social. Cas de la ville de M'sila, Algérie (Analele Universității București.Geografie, 2025)
Our research emanates from the design and use of social housing in Algeria; His analysis was based on the post-occupational evaluation approach, in order to assess the spatial architectural quality of housing and to measure the degree of satisfaction of its users. This method offers three levels of assessment; namely the indicative level, the level of investigation and the diagnostic level. Through this article, we will show the reference model on which the design of housing in Algeria is based. Know the design criteria and the constraints that hinder the actors of the act of building to carry out their missions by adopting the method of content analysis. The analysis tool used is the semi-structured interview carried out with officials responsible for the design and management of social rental housing in M'sila.